The Impact of Political Instability on Financial Development, Economic Growth, Economic Growth Volatility and Financial Stability in Developing Countries - ULLAH, Wasim; ZUBIR, Ahmad Shauqi Mohamad; ARIFF, Akmalia Mohamad (Theoretical and Practical Research in Economic Fields, 2024)
Political instability is usually attributed to the disruption of policy continuity following regime changes. Moreover, it is not solely the tangible effect but also the perceived risk among investors and other stakeholders that will result in policy alterations. Furthermore, the frequency and the manner in which regime changes occur play a crucial role in shaping the economic repercussions. This study fills in the gap in the literature by exploring the impact of political stability (PS) on financial development (FD), economic growth (EG), economic growth volatility (EGV) and financial stability (FS). This study uses the PCSE estimation method with a robustness check of GMM on data for 33 developing countries from 1980-2020. Results are useful for macro-prudential and macroeconomic policymakers. First, the relationship of PS with FD is linear for both financial institutions and financial markets. However, financial market efficiency (FME) reduces with increased PS. Therefore, policymakers need to focus on regulating FME related practices in politically stable environments. Second, PS positively affects EG in developing countries. Third, PS reduces EGV in developed countries, yet it increases economic growth volatility for developing countries. The policymakers in developing countries should not only be focused on financialization but they must also ensure that the reforms in enabling environment are also keeping pace with the growth of financialization. Fourth, PS increases FS for developing countries. Hence, economic growth volatility and financial stability cannot be used synonymously as these are measured differently and FS is a sub-set of economic stability. Therefore, the policy makers need to formulate the policies related to each of them according to the market and institutional realities pertaining to each of them.